The influence of service quality on customer patronage intention: the moderating ‎effects of firm's image - Rahman, Muhammad Sabbir; Abdel Fattah, Fadi Abdel Muniem (2016)
This article seeks to introduce the influence of service quality on customer patronage intention of exploring the moderating role of firm’s image from the perspective of health insurance customers. In testing the hypotheses this research applied a self-administered survey technique to collect the data from the customers of health care insurance service providers from the Klang Valley area, Malaysia. Structural ‎Equation Modelling (SEM) approach was used to analyze and test relationships among proposed variables. The findings of this study indicated that all paths of the proposed relationship were significant. Despite that the mediation impact of customers' satisfaction was partial rather full. Moreover, the result also revealed that there is a moderating influence of firm's image in the relationship between customers' satisfaction and customers’ patronage intention. Since there was a lack of such research in Malaysian healthcare insurance context, this study can provide theoretical contribution and a managerial basis for future researchers as well as implications for the managers.